EDUCATIONAL COMICS AS A VISUAL MEDIUM: POTENTIALS AND IMPLICATIONS FOR PUPILS WITH LEARNING DISABILITIES - Yusuf, Yuzaila; Rashid, Syar Meeze Mohd; Nordin, Mohd Norazmi; Yahya, Siti Farisah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Comics are increasingly recognised as a promising educational medium that integrates visuals and text to convey knowledge in an accessible, engaging and meaningful way. Unlike conventional text-heavy materials, comics provide a multimodal learning experience that draws on the strengths of both linguistic and visual representation. For pupils with learning disabilities (LD), including dyslexia, Attention Deficit Hyperactivity Disorder (ADHD) and autism spectrum conditions, such resources are especially valuable. Traditional instructional texts often create barriers to reading fluency, comprehension and motivation, whereas comics offer structured scaffolding through sequential panels, simplified dialogue and expressive imagery. These features can reduce cognitive load, sustain attention and foster active engagement with content. This concept paper explores the potential of educational comics as a visual medium by examining the global history and evolution of comics as a form of communication, their categorisation into narrative, informative and educational types, and their pedagogical relevance for pupils with LD. Several theoretical perspectives guide this exploration, including Dual Coding Theory, Cognitive Load Theory, Automaticity Theory and Self-Determination Theory. Based on these foundations, a conceptual framework is proposed to illustrate how comics can support learning processes and outcomes. The framework highlights the contributions of comics to reading fluency, comprehension, motivation and socio-emotional development. The discussion also considers potential challenges in adopting comics within special education, particularly issues of teacher preparedness, curricular alignment and the availability of appropriate resources. Nevertheless, the inclusive and motivating nature of comics positions them as valuable pedagogical tools for promoting accessible, equitable and engaging education for diverse pupils. This positions educational comics not merely as supplementary resources but also as transformative tools for inclusive education.